AYAT-AYAT TAMTSÎL AL-QUR`AN (ANALISIS STILISTIKA) - Bustami, Hafni (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
The Quran is the highest miracle (mu`jizat) of Prophet Muhammad (Peace be upon Him). Its strength lies in two aspects; content and linguistic. The God and the Prophet have encouraged the Moslem to comprehend similitude verses of the Quran (tamtsîl) since it provides countless benefits. It is found through this research that the style of similitude verses (sharîh, mursal and kâminah) were written in 168 verses. Based on the language style, tamtsîl is classified into sharîh, mursal dan kâminah. Meanwhile, the benefits of the similitude verses for mankind are: targhîb, tarhîb, tahzîr, mau’izhah and i’tibâr.